2021
DOI: 10.37010/duconomics.v1.5412
|View full text |Cite
|
Sign up to set email alerts
|

Online Lecture Model with WhatsApp Group (WaG) and Google Classroom (GC) Integration

Abstract: The impact of Covid-19 has made educational institutions carry out online learning processes; thus, they must provide innovative learning media so that students continue to get material explanations like in face-to-face learning. This study aims to design and evaluate an online lecture model by integrating WaG and GC. Using descriptive method, this study involves Economic Education students at Universitas Indraprasta PGRI for the academic year 2020/2021 who received 276 scientific writing courses. This study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…36962/MPK.A/HK/2020 requiring that learning both in schools and in universities be carried out online. Research showed that a variety of online learning models have been in place in universities across the globe, mostly using the smartphone as a platform (Muthuprasad, Aiswarya, Aditya, & Jha, 2021) and utilising Zoom video conferencing application (Islam, Kim, & Kwon, 2020), WhatsApp and Google Classroom (Saputra, 2021;Zhafira, Ertika, & Chairiyaton, 2020) for providing instruction. This is similar to what school counselors do in general who use Google Classroom and Google Forms for classical guidance services, and WhatsApp for individual and group counseling services (Hastuti & Tyas, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…36962/MPK.A/HK/2020 requiring that learning both in schools and in universities be carried out online. Research showed that a variety of online learning models have been in place in universities across the globe, mostly using the smartphone as a platform (Muthuprasad, Aiswarya, Aditya, & Jha, 2021) and utilising Zoom video conferencing application (Islam, Kim, & Kwon, 2020), WhatsApp and Google Classroom (Saputra, 2021;Zhafira, Ertika, & Chairiyaton, 2020) for providing instruction. This is similar to what school counselors do in general who use Google Classroom and Google Forms for classical guidance services, and WhatsApp for individual and group counseling services (Hastuti & Tyas, 2021).…”
Section: Introductionmentioning
confidence: 99%